Big Nate : blasts off - Peirce, Lincoln (Balzer + Bray, an imprint of HarperCollinsPublishers, 2021)
"After his fight with Randy Betancourt makes headlines in the school paper, Big Nate has a problem worse than detention on his hands."--Provided by publisher